Possessives with kinship terms in Italian and Italo-Romance dialects - Francesca Volpato; Gianluca Lebani (Isogloss)
This study investigates the acceptability of constructions containing third-person possessives combined with singular and plural kinship terms in adult bilectal speakers of Italian and different Italo-Romance varieties spoken in six different geographic areas in northern, central, and southern Italy. The sentences to be judged vary according to the presence and position (prenominal vs. postnominal) of the possessive and the presence vs. absence of the definite article. For Italian, results were consistent with the patterns highlighted by previous studies. For the six dialects, much more variation and optionality were observed. Comparing the results of our questionnaire to data reported in AIS maps (Jaberg and Jud [1928] 1940), we found a situation that only partially replicated the picture presented in these documents in the first half of the last century. Regarding contact issues, we found cases of the influence of the dialect on Italian, instances of the influence of Italian on the dialect, and cases where the dialects have changed independently of Italian. By investigating whether participants’ language dominance modulated the acceptability of certain patterns, we found some influence of Italian on the dialect only for speakers with Italian dominance.